2020
DOI: 10.1080/13563467.2020.1841145
|View full text |Cite
|
Sign up to set email alerts
|

The Trade (Policy) Discourse in Top Economics Journals

Abstract: In the aftermath of recent populist upheavals in Europe, nationalist economic policies challenge the overly positive view on economic integration and the reduction of trade barriers established by standard economic theory. For quite a long time the great majority of economists supported trade liberalisation policies, at least those actively engaged in policy advice or public debates. In this paper, we examine the elite economics discourse on trade policies during the last 20 years regarding specific characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…To obtain representative data of the elite discourse in economics related to trade, we use two different data samples, compiled for a recent paper on the structure of the elite trade discourse in economics (Aistleitner and Pühringer 2021). This sample contains a total of 422 trade-related elite economic papers, among them 372 papers (88%) published in top 5 and 50 highly cited papers published in a set of 16 highimpact economic journals.…”
Section: Methodological Framework and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain representative data of the elite discourse in economics related to trade, we use two different data samples, compiled for a recent paper on the structure of the elite trade discourse in economics (Aistleitner and Pühringer 2021). This sample contains a total of 422 trade-related elite economic papers, among them 372 papers (88%) published in top 5 and 50 highly cited papers published in a set of 16 highimpact economic journals.…”
Section: Methodological Framework and Datamentioning
confidence: 99%
“…Beyer and Pühringer 2022;Fuller and Geide-Stevenson 2014;Gordon and Dahl 2013) 2 and more recently, by studies focusing on the economic elite that manifests in research published in top 5 and other prestigious economic outlets (Aistleitner and Pühringer 2021). With regard to the latter, Aistleitner and Pühringer (2021) have also shown that within elite economic trade debate otherthan-economic impacts and implications of trade policies (political, social and cultural as well as environmental issues) to a great extent either remain unmentioned or are rationalized by means of pure economic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to "combine the composition technology theory course and art teaching practice for music education majors in normal colleges". Learning composition theory, it is also necessary to combine music skills with practical applications [17].…”
Section: Related Workmentioning
confidence: 99%
“…Bernard et al (2012) and Wagner (2016) provide a summary of empirical evidence on firms in international trade. Aistleitner and Puehringer (2020) describes the trajectory of trade discourse in elite journals of economics in the past two decades.…”
Section: Introductionmentioning
confidence: 99%